Preparation method of composite carrier loaded platinum-based catalyst
By using a platinum-based catalyst prepared with nanozirconia and porous carbon as composite support, the problem of insufficient activity and durability of platinum-carbon catalysts under different humidity conditions in the prior art is solved, and high activity and high durability performance under dry and wet and wide conditions are achieved.
Patent Information
- Application Number
- CN202510036166.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing carbon black-supported platinum carbon catalysts are difficult to maintain high activity and durability under different humidity conditions, which affects the working efficiency of fuel cells.
Nanozirconia and porous carbon are used as composite support, and a platinum-based catalyst is prepared through heat treatment and dealloyment treatment to adjust its adaptability to dry and wet conditions.
The catalyst accelerates the discharge rate of water on the membrane electrode surface under high humidity conditions, reduces the dissolution rate of metal ions, and improves activity and durability; improves the water retention capacity of the catalytic layer and the transmission speed of protons under low humidity conditions, and improves the kinetics of the electrochemical reaction.
Smart Images

Figure CN119833650A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical energy, and relates to a method for preparing a composite carrier-loaded platinum-based catalyst. Background Art
[0002] The commercialization of proton exchange membrane fuel cells has put forward higher requirements on the performance of fuel cells in dry and wet conditions. The water in the proton exchange membrane is the channel for proton transmission. If the water retention of the catalyst layer is too low, it will affect the effective transmission of protons, thereby reducing the working efficiency of the fuel cell; if the water retention of the catalyst layer is too high, it will cause flooding of the catalyst layer, which is not conducive to the electrochemical reaction kinetics. In actual fuel cell applications, in order to improve the performance of fuel cells in dry and wet conditions, the adaptability and stability of fuel cells to different humidity conditions can be improved by selecting suitable catalyst materials, designing the catalyst layer structure and optimizing the system design.
[0003] At present, cathode catalysts are mainly platinum-carbon catalysts with carbon black as the carrier. Since carbon black has fewer oxygen-containing functional groups on its surface, it exhibits a certain degree of hydrophobicity. During battery operation, it is difficult for platinum-carbon catalysts to exhibit high activity and high durability under different humidity conditions. In view of this, this patent proposes a method for preparing a composite carrier-loaded platinum-based catalyst that can be applied to a wide range of dry and wet conditions, and designs a composite carrier of nano-zirconium oxide and porous carbon to improve its adaptability to different humidity conditions; a platinum-based catalyst is prepared based on the composite carrier. Under high humidity conditions, the catalyst can accelerate the discharge rate of water generated on the membrane electrode surface and reduce the dissolution rate of metal ions in the catalyst, thereby improving the high activity and high durability of the catalyst; under low humidity conditions, the catalyst can improve the water retention capacity of the catalyst layer and accelerate the effective transmission rate of protons in the catalyst layer, thereby improving the electrochemical reaction kinetics of the catalyst. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a composite carrier-supported platinum-based catalyst, which has the characteristics of simple process and batch preparation.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a composite carrier-supported platinum-based catalyst, the specific process of the catalyst preparation method is as follows:
[0007] S1: Evenly dispersing nano zirconium oxide, a pore former, and a carbon precursor in a mass ratio of 100:(2-20):(20-100) in a reaction kettle to obtain a mixture A;
[0008] S2: In an argon atmosphere, the mixture A is reacted in a reactor at a constant temperature of 150-250° C. for 2-4 hours with a stirring speed of 300 r / min to obtain a mixture B;
[0009] S3: Under an argon atmosphere, the stirring speed of the reactor was adjusted to 150 r / min, and the mixture B was continued to be reacted at a constant temperature of 250-450° C. in the reactor for 2-4 hours to obtain a mixture C;
[0010] S4: Under an argon atmosphere, the reaction temperature is raised to 900° C., and the mixture C is further heat-treated for 2 h to obtain a composite carrier D;
[0011] S5: The composite carrier D is dispersed in deionized water, and ultrasonicated for 1 hour to obtain a dispersion E with a mass fraction of 10%, and a transition metal salt aqueous solution with a mass fraction of 30% is added to the dispersion E, wherein the mass ratio of the transition metal salt to the composite carrier D is 3:10, and the mixture is evenly mixed and heated at 90°C for 5 hours to obtain a mixed slurry, and the mixed slurry is dried at 110°C for 12 hours to obtain a solid mixture, and the solid mixture is ground into particles, and heat-treated at 800°C for 2 hours in an argon atmosphere to obtain a composite material F;
[0012] S6: dispersing platinum salt in deionized water to obtain a platinum salt dispersion G with a mass fraction of 25%, dissolving composite material F in an organic solvent to obtain a composite material F solution with a concentration of 6 g / L, and then adding the prepared platinum salt dispersion G to the composite material F solution, wherein the molar ratio of platinum to the transition metal in the composite material F is 3.5:1, continuously stirring, heating at 120°C for 12h, cooling and filtering, drying at 80°C for 12h, and grinding to obtain composite material H;
[0013] S7: The obtained composite material H is heat treated at 900°C for 3 hours in a hydrogen-argon mixed gas atmosphere to obtain a composite material I, and then the composite material I is immersed in a nitric acid solution and dealloyed at 80-100°C for 12-48 hours. After the treatment, it is filtered, dried, and ball-milled to obtain the catalyst.
[0014] Furthermore, the average particle size of the nano zirconium oxide in S1 is 20nm to 500nm.
[0015] Furthermore, the pore-forming agent in S1 is one or more of azodicarbonamide, diisopropyl azodicarboxylate, ammonium oxalate, ammonium bicarbonate, ammonium nitrate, and lithium carbonate.
[0016] Furthermore, the carbon precursor in S1 is one or more of polyethylene glycol, polyacrylic acid, polydopamine, polystyrene, sucrose, starch, chitosan, asphalt, and resin.
[0017] Furthermore, the transition metal salt in S5 is one or more of cobalt nitrate, manganese nitrate, nickel nitrate, iron nitrate, palladium nitrate, gold nitrate, copper nitrate, chromium nitrate, and iridium nitrate.
[0018] Furthermore, the platinum salt in S6 is chloroplatinic acid.
[0019] Furthermore, the organic solvent in S6 is one or more of ethylene glycol, propylene glycol, and pentaerythritol.
[0020] Furthermore, the concentration of the nitric acid solution in S7 is 0.5M to 1M.
[0021] Furthermore, the gas volume percentage of the hydrogen-argon mixed gas in S7 is (5-10)% H2+(90-95)% Ar.
[0022] Furthermore, the pore structure size of the catalyst carbon carrier prepared in S7 is between 3nm and 500nm, and the particle size of the platinum alloy is between 2nm and 10nm.
[0023] The present invention provides a method for preparing a composite carrier-supported platinum-based catalyst applicable to a wide range of dry and wet working conditions, the preparation method comprising the following steps:
[0024] (1) Nano-zirconia, pore-forming agent and carbon precursor are dispersed uniformly in a reactor to obtain mixture A; (2) Mixture A is continuously heated and cross-linked in a reactor under a protective atmosphere to obtain mixture B; (3) Mixture B is continuously thermally decomposed and pore-formed in a reactor under a protective atmosphere to obtain mixture C; (4) Mixture C is continuously carbonized at high temperature under a protective atmosphere to obtain a composite carrier D; (5) A platinum-based catalyst is directly prepared by a one-step method using the composite carrier D. The catalyst can significantly adjust its adaptability to dry and wet working conditions by adjusting the mass ratio of the hydrophilic metal oxide to the hydrophobic carbon carrier.
[0025] The present invention prepares a composite carrier with special structure and performance through a combination of nano zirconium oxide, pore-forming agent and carbon precursor, and undergoes a series of heat treatments. This carrier has a high specific surface area, good pore structure and chemical stability, which is conducive to the dispersion and stability of platinum-based catalysts. The present invention adds a carbon precursor to the carrier to improve the activity of the catalyst. The carbon material has a high specific surface area, which is conducive to the dispersion of platinum nanoparticles, increases the active sites of the catalyst, and thus improves the catalytic efficiency; the carbon material has good mechanical strength and chemical stability, and can protect the platinum nanoparticles from agglomeration or dissolution under harsh conditions such as high temperature and high pressure, thereby extending the service life of the catalyst; by adding a pore-forming agent and adjusting the reaction conditions, a composite carrier with a porous structure can be obtained, which is conducive to the mass transfer of reactants and the diffusion of products, and improves the efficiency of the catalytic reaction.
[0026] Nano zirconium oxide is a metal oxide with acidity, alkalinity, oxidizability and reducibility. The average particle size can be controlled at about 50nm. As a p-type semiconductor, it is easy to generate oxygen vacancies. Compared with carbon black carriers, nano zirconium oxide is used as a fuel cell cathode catalyst carrier, which can enhance the interaction between the active component and the carrier, thereby effectively improving the performance of the catalyst. In addition, by introducing nano zirconium oxide into a carbon carrier, the wettability and hydrophilicity of the composite carrier can also be effectively improved. Therefore, the platinum-based catalyst prepared by the present invention using nano zirconium oxide and porous carbon as a composite carrier can effectively improve the activity and compatibility of the platinum-based catalyst in a wide range of dry and wet working conditions.
[0027] The introduction of transition metals in the catalyst preparation can further improve the catalytic performance and stability of the catalyst through the interaction between transition metals and platinum. Platinum salts are loaded in the form of a dispersion to ensure the uniform distribution of platinum on the carrier. At the same time, the structure and performance of the catalyst can be further optimized through subsequent heat treatment and dealloying treatment.
[0028] There is electron transfer and sharing between transition metals and platinum, which will cause changes in the electronic structure of platinum. The d-band center position of transition metals is different from that of platinum. When they form an alloy, the d-band center will move. This movement can affect the adsorption energy and activation energy of the catalyst surface for reactants, thereby optimizing the catalytic performance.
[0029] The addition of transition metals can change the morphology, size and distribution of platinum particles. The optimized platinum particle structure can provide more active sites, which is conducive to the catalytic reaction. Since the lattice parameters of transition metals and platinum are different, when they are closely combined, lattice distortion will occur. Lattice distortion can change the number and distribution of active sites on the catalyst surface, thereby affecting the catalytic activity.
[0030] Beneficial effects of the present invention:
[0031] The composite carrier structure obtained by the combination design of nano zirconium oxide and porous carbon in the present invention can effectively broaden the matching window of the catalyst carrier to the dry and wet working conditions of the fuel cell;
[0032] The present invention uses nano-zirconium oxide and porous carbon as a composite carrier to prepare a platinum-based catalyst, which can effectively improve the activity and compatibility of the platinum-based catalyst under a wide range of dry and wet working conditions. The preparation method has the advantages of simple process and batch preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0034] Figure 1 A schematic diagram of the structure of the composite carrier prepared in Example 1 of the present invention;
[0035] Figure 2 The battery performance of the alloy catalysts prepared in Example 1 of the present invention and Comparative Examples 1-2 under low humidity conditions (25% humidity / 80°C);
[0036] Figure 3 The battery performance of the alloy catalysts prepared in Example 1 of the present invention and Comparative Examples 1-2 under high humidity conditions (95% humidity / 42° C.). DETAILED DESCRIPTION
[0037] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0038] Example 1
[0039] S1: Weigh 50 g of nano zirconium oxide (average particle size 50 nm), 1 g of azodicarbonamide, and 80 g of soluble starch respectively, stir and disperse them evenly in a reaction kettle to obtain a mixture A;
[0040] S2: In an argon atmosphere, the mixture A was reacted at 150° C. for 4 h in a 10 L reactor with a stirring speed of 300 r / min to obtain a mixture B;
[0041] S3: Under an argon atmosphere, the stirring speed of the reactor was adjusted to 150 r / min, and the mixture B was continued to be reacted at 400° C. in the reactor for 2 h to perform thermal decomposition and pore formation to obtain a mixture C;
[0042] S4: Under an argon atmosphere, the reaction temperature is raised to 900° C., and the mixture C is further heat-treated for 2 h to obtain a composite carrier D;
[0043] S5: 10 g of composite carrier D was dispersed in deionized water, and ultrasonicated for 1 h to obtain a dispersion E with a mass fraction of 10%. A 30% cobalt nitrate aqueous solution was added to the dispersion E, wherein the mass ratio of cobalt nitrate to composite carrier D was 3:10. After mixing evenly, the mixture was heated at 90° C. for 5 h to obtain a mixed slurry. The mixed slurry was dried at 110° C. for 12 h to obtain a solid mixture. The solid mixture was ground into particles, and heat-treated at 800° C. for 2 h in an argon atmosphere to obtain a composite material F.
[0044] S6: 24.9 g of chloroplatinic acid was dispersed in deionized water to obtain a chloroplatinic acid dispersion G with a mass fraction of 25%, the composite material F was dissolved in 500 ml of ethylene glycol to obtain a composite material F solution with a concentration of 6 g / L, and the prepared platinum salt dispersion G was added to the composite material F solution, wherein the molar ratio of platinum to the transition metal in the composite material F was 3.5:1, the mixture was continuously stirred, heated at 120°C for 12 h, cooled and filtered, dried at 80°C for 12 h, and ground to obtain the composite material H;
[0045] S7: The obtained composite material H is heat treated at 900°C for 3 hours in a hydrogen-argon mixed gas atmosphere with a gas volume percentage of 10% H2+90% Ar to obtain a composite material I, and then the composite material I is immersed in a 1M nitric acid solution and dealloyed at 80°C for 48 hours. After the treatment, it is filtered, dried, and ball-milled to obtain the Pt-Co / C alloy catalyst.
[0046] In the Pt-Co / composite carrier alloy catalyst prepared in this embodiment, the alloy particles are evenly distributed on the carbon material, and the average particle size is 4.5 nm. The battery performance of the alloy catalyst under low humidity conditions (25% humidity / 80°C) is as follows: Figure 2 As shown, the corresponding test standard is the electrocatalyst test method in GB / T20042.4-2009; the battery performance of the alloy catalyst under high humidity conditions (95% humidity / 42°C) is shown Figure 3 As shown, the corresponding test standard is the electrocatalyst test method in GB / T20042.4-2009.
[0047] Example 2
[0048] S1: Weigh 50 g of nano zirconium oxide (average particle size 100 nm), 5 g of diisopropyl azodicarboxylate, and 100 g of polyacrylic acid respectively, stir and disperse them evenly in a reaction kettle to obtain a mixture A;
[0049] S2: Under argon atmosphere, mixture A was reacted at 250° C. for 2 h in a 10 L reactor with a stirring speed of 300 r / min to obtain mixture B;
[0050] S3: Under argon atmosphere, the stirring speed of the reactor was adjusted to 150 r / min, and the mixture B was continued to be reacted at 350° C. in the reactor for 4 h to perform thermal decomposition and pore formation to obtain a mixture C;
[0051] S4: Under an argon atmosphere, the reaction temperature is raised to 900° C., and the mixture C is further heat-treated for 2 h to obtain a composite carrier D;
[0052] S5: 10 g of composite carrier D was dispersed in deionized water, and ultrasonicated for 1 h to obtain a dispersion E with a mass fraction of 10%. A 30% cobalt nitrate aqueous solution was added to the dispersion E, wherein the mass ratio of cobalt nitrate to composite carrier D was 3:10. After mixing evenly, the mixture was heated at 90° C. for 5 h to obtain a mixed slurry. The mixed slurry was dried at 110° C. for 12 h to obtain a solid mixture. The solid mixture was ground into particles, and heat-treated at 800° C. for 2 h in an argon atmosphere to obtain a composite material F.
[0053] S6: 24.9 g of chloroplatinic acid was dispersed in deionized water to obtain a chloroplatinic acid dispersion G with a mass fraction of 25%, the composite material F was dissolved in 500 ml of ethylene glycol to obtain a composite material F solution with a concentration of 6 g / L, and the prepared platinum salt dispersion G was added to the composite material F solution, wherein the molar ratio of platinum to the transition metal in the composite material F was 3.5:1, the mixture was continuously stirred, heated at 120°C for 12 h, cooled and filtered, dried at 80°C for 12 h, and ground to obtain the composite material H;
[0054] S7: The obtained composite material H is heat treated at 1000°C for 1 h in a hydrogen-argon mixed gas atmosphere with a gas volume percentage of 5% H2+95% Ar to obtain a composite material I, and then the composite material I is immersed in a 0.5M nitric acid solution and dealloyed at 100°C for 24 h. After the treatment, it is filtered, dried, and ball-milled to obtain the Pt-Co / C alloy catalyst.
[0055] Example 3
[0056] S1: Weigh 50 g of nano zirconium oxide (average particle size 200 nm), 10 g of lithium carbonate, and 80 g of sucrose respectively, stir and disperse them evenly in a reaction kettle to obtain a mixture A;
[0057] S2: In an argon atmosphere, the mixture A was reacted in a 10 L reactor at 160° C. for 4 h with a stirring speed of 300 r / min to obtain a mixture B;
[0058] S3: Under an argon atmosphere, the stirring speed of the reactor was adjusted to 150 r / min, and the mixture B was continued to be reacted at 450° C. in the reactor for 2 h to perform thermal decomposition and pore formation to obtain a mixture C;
[0059] S4: Under an argon atmosphere, the reaction temperature is raised to 900° C., and the mixture C is further heat-treated for 2 h to obtain a composite carrier D;
[0060] S5: 10 g of composite carrier D was dispersed in deionized water, and ultrasonicated for 1 h to obtain a dispersion E with a mass fraction of 10%. A 30% cobalt nitrate aqueous solution was added to the dispersion E, wherein the mass ratio of cobalt nitrate to composite carrier D was 3:10. After mixing evenly, the mixture was heated at 90° C. for 5 h to obtain a mixed slurry. The mixed slurry was dried at 110° C. for 12 h to obtain a solid mixture. The solid mixture was ground into particles, and heat-treated at 800° C. for 2 h in an argon atmosphere to obtain a composite material F.
[0061] S6: 24.9 g of chloroplatinic acid was dispersed in deionized water to obtain a chloroplatinic acid dispersion G with a mass fraction of 25%, the composite material F was dissolved in 500 ml of ethylene glycol to obtain a composite material F solution with a concentration of 6 g / L, and the prepared platinum salt dispersion G was added to the composite material F solution, wherein the molar ratio of platinum to the transition metal in the composite material F was 3.5:1, the mixture was continuously stirred, heated at 120°C for 12 h, cooled and filtered, dried at 80°C for 12 h, and ground to obtain the composite material H;
[0062] S7: The obtained composite material H is heat treated at 1000°C for 1 h in a hydrogen-argon mixed gas atmosphere with a gas volume percentage of 10% H2+90% Ar to obtain a composite material I, and then the composite material I is immersed in a 0.5M nitric acid solution and dealloyed at 90°C for 12 h. After the treatment, it is filtered, dried, and ball-milled to obtain the Pt-Co / C alloy catalyst.
[0063] Comparative Example 1
[0064] S1: Weigh 10 g of nano zirconium oxide (average particle size 100 nm), disperse it in deionized water under ultrasonic conditions to obtain a dispersion, add an aqueous solution containing 3.1 g of cobalt nitrate to the dispersion, heat it at 100° C. for 2 h to form a slurry, continue drying and ball milling, and then heat treat it at 900° C. for 2 h in an argon atmosphere to obtain a composite material;
[0065] S2: According to the molar ratio of metal platinum to transition metal of 3.5:1, prepare an aqueous solution containing 24.9g of chloroplatinic acid, add the obtained chloroplatinic acid dispersion to 500ml of ethylene glycol dispersion of the composite material prepared in S1, continue stirring and heat at 120°C for 12h, then filter, dry and ball-mill to obtain a composite material;
[0066] S3: The composite material obtained in S2 is heat treated at 1000°C for 1 hour in a hydrogen-argon mixed gas containing 10% by volume of hydrogen to obtain a composite material H, and then the composite material H is further dealloyed in a 0.5M nitric acid solution at 90°C for 12 hours, and then filtered, dried, and ball-milled to obtain a Pt-Co / zirconia alloy catalyst.
[0067] The support used in this Comparative Example 1 does not contain a carbon material.
[0068] Comparative Example 2
[0069] S1: Weigh 10 g of high-surface-area carbon black, disperse it in deionized water by ultrasonication to obtain a dispersion, add an aqueous solution containing 3.1 g of cobalt nitrate to the dispersion, heat it at 100° C. for 2 h to form a carbon slurry, continue drying and ball milling, and then heat treat it at 900° C. for 2 h in an argon atmosphere to obtain a composite material;
[0070] S2: Prepare an aqueous solution containing 24.9 g of chloroplatinic acid according to the molar ratio of metal platinum to transition metal of 3.5:1, add the obtained chloroplatinic acid dispersion to 500 ml of ethylene glycol dispersion of the composite material prepared in S1, continue stirring and heat at 120°C for 12 hours, then filter, dry and ball-mill to obtain the composite material.
[0071] S3: The composite material obtained in S2 was heat treated at 1000°C for 1 hour in a hydrogen-argon mixed gas containing 10% by volume of hydrogen to obtain a composite material H. The composite material H was then dealloyed in a 0.5M HNO3 solution at 90°C for 12 hours, filtered, dried, and ball-milled to obtain a Pt-Co / C alloy catalyst.
[0072] The carbon support used in this Comparative Example 2 does not contain zirconium oxide.
[0073] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite carrier-supported platinum-based catalyst, characterized in that: The specific process of the preparation method of the catalyst is as follows: S1: Evenly dispersing nano zirconium oxide, a pore former, and a carbon precursor in a mass ratio of 100:(2-20):(20-100) in a reaction kettle to obtain a mixture A; S2: In an argon atmosphere, the mixture A is reacted in a reactor at a constant temperature of 150-250° C. for 2-4 hours with a stirring speed of 300 r / min to obtain a mixture B; S3: Under an argon atmosphere, the stirring speed of the reactor was adjusted to 150 r / min, and the mixture B was continued to be reacted at a constant temperature of 250-450° C. in the reactor for 2-4 hours to obtain a mixture C; S4: Under an argon atmosphere, the reaction temperature is raised to 900° C., and the mixture C is further heat-treated for 2 h to obtain a composite carrier D; S5: The composite carrier D is dispersed in deionized water, and ultrasonicated for 1 hour to obtain a dispersion E with a mass fraction of 10%, and a transition metal salt aqueous solution with a mass fraction of 30% is added to the dispersion E, wherein the mass ratio of the transition metal salt to the composite carrier D is 3:10, and the mixture is evenly mixed and heated at 90°C for 5 hours to obtain a mixed slurry, and the mixed slurry is dried at 110°C for 12 hours to obtain a solid mixture, and the solid mixture is ground into particles, and heat-treated at 800°C for 2 hours in an argon atmosphere to obtain a composite material F; S6: dispersing platinum salt in deionized water to obtain a platinum salt dispersion G with a mass fraction of 25%, dissolving composite material F in an organic solvent to obtain a composite material F solution with a concentration of 6 g / L, and then adding the prepared platinum salt dispersion G to the composite material F solution, wherein the molar ratio of platinum to the transition metal in the composite material F is 3.5:1, continuously stirring, heating at 120°C for 12h, cooling and filtering, drying at 80°C for 12h, and grinding to obtain composite material H; S7: The obtained composite material H is heat treated at 900°C for 3 hours in a hydrogen-argon mixed gas atmosphere to obtain a composite material I, and then the composite material I is immersed in a nitric acid solution and dealloyed at 80-100°C for 12-48 hours. After the treatment, it is filtered, dried, and ball-milled to obtain the catalyst.
2. The method for preparing a composite carrier-supported platinum-based catalyst according to claim 1, characterized in that: The average particle size of the nano zirconium oxide in S1 is 20nm to 500nm.
3. The method for preparing a composite carrier-supported platinum-based catalyst according to claim 1, characterized in that: The pore-forming agent in S1 is one or more of azodicarbonamide, diisopropyl azodicarboxylate, ammonium oxalate, ammonium bicarbonate, ammonium nitrate, and lithium carbonate.
4. The method for preparing a composite carrier-supported platinum-based catalyst according to claim 1, characterized in that: The carbon precursor in S1 is one or more of polyethylene glycol, polyacrylic acid, polydopamine, polystyrene, sucrose, starch, chitosan, asphalt, and resin.
5. The method for preparing a composite carrier-supported platinum-based catalyst according to claim 1, characterized in that: The transition metal salt in S5 is one or more of cobalt nitrate, manganese nitrate, nickel nitrate, iron nitrate, palladium nitrate, gold nitrate, copper nitrate, chromium nitrate, and iridium nitrate.
6. The method for preparing a composite carrier-supported platinum-based catalyst according to claim 1, characterized in that: The platinum salt in S6 is chloroplatinic acid.
7. The method for preparing a composite carrier-supported platinum-based catalyst according to claim 1, characterized in that: The organic solvent in S6 is one or more of ethylene glycol, propylene glycol and pentaerythritol.
8. The method for preparing a composite carrier-supported platinum-based catalyst according to claim 1, characterized in that: The concentration of the nitric acid solution in S7 is 0.5M to 1M.
9. The method for preparing a composite carrier-supported platinum-based catalyst according to claim 1, characterized in that: The gas volume percentage of the hydrogen-argon mixed gas in S7 is (5-10)% H2+(90-95)% Ar.
10. The method for preparing a composite carrier-supported platinum-based catalyst according to claim 1, characterized in that: The pore structure size of the catalyst carbon carrier prepared in S7 is 3nm to 500nm, and the particle size of the platinum alloy is 2nm to 10nm.
Citation Information
Patent Citations
Aluminum, zirconium and carbon composite carrier sulfur-tolerant shift catalyst and preparation method thereof
CN106552634A
Ceramic-based catalyst for synergistically removing NO and chlorobenzene as well as preparation method and application of ceramic-based catalyst
CN117654531A
Catalytic layer of fuel cell as well as preparation method and application of catalytic layer
CN118825289A
Zirconium oxide composite carrier for vacuum evaporation and preparation method thereof
CN119161205A
coating of substrates while ensuring high porosity while maintaining high abrasion resistance of the coating
DE102007048313A1